THE ASSOCIATION BETWEEN DEPRESSIVE SYMPTOMS & COGNITION DIFFERS BY AGE BUT NOT BY ALZHEIMER'S GENETIC RISK OR GENDER. (16th November 2018) - Jonsdottir, H; Arpawong, T; Jones, R; Chanti-Ketterl, M; Harrati, A; Medina, L; Manly, J; Williams, M
Abstract: Depression associates with poorer cognitive ability and accelerated cognitive decline in older adults, particularly in women. Among younger adults, gender, age, and genetic risk for Alzheimer's disease (AD) modify the association, but it is uncertain whether this is true in older adults. In this study, we examine whether the relationship between depressive symptoms (DepSym) and cognition (1) is attenuated by genetic risk for AD, and differs by gender and age; and (2) strengthens in the same individuals as they age. Data come from the U.S. Health and Retirement Study (HRS) with ~9, 000 participants surveyed between 1996–2012. Measures included immediate and delayed verbal memory, total cognitive ability, DepSym, age, gender, and genetic risk for AD. Genetic risk was indexed by both APOE e4 allele and AD polygenic risk score. Cross-sectional linear regression showed DepSym associated inversely with immediate verbal memory (β = -0.09, p<.001) and total cognition (β = -0.12, p<.001), but not delayed memory; neither gender nor genetic risk for AD altered the associations. Age moderated the relationship between DepSym and immediate verbal memory (interaction β=-0.02, p<.05). In longitudinal analysis with 16 years of follow-up, age moderated the association between DepSym and immediate memory (F(1, 8869)=16.9, b=-.03, p<.001) and total cognition (F(1, 8319)=16.7, b=-.10, p<.001) over time, with stronger associations when individuals were age ≥75 versus when <75 for immediate memory (b=-0.09 and b=-0.04, respectively) and total cognition (b=-0.25 and b=-0.13, respectively). Findings emphasize the importance of assessing and treating depressive symptoms, especially among those in older ages.